Molecular Elucidation of Anthocyanin Accumulation Mechanisms in Hippeastrum hybridum Cultivars - Pengyu Guo; Chuanji Xing; Jiacheng Ye; Jing Xue; Luis A. J. Mur; Bao Di; Zongli Hu; Guoping Chen; Xiuhai Zhang; Xuqing Chen (Agronomy)
Hippeastrum, a perennial herbaceous plant belonging to the Amaryllidaceae family, is widely cultivated for its large, vibrant flowers with diverse petal colors, which have significant ornamental and economic value. However, the mechanisms underlying anthocyanin accumulation in Hippeastrum petals remain poorly understood. To fully explore the involved regulation mechanism was significant for the breeding of Hippeastrum and other Amaryllidaceae family plants. In this study, we selected six Hippeastrum cultivars with distinctly different petal colors. We used metabolomic profiling and high-throughput transcriptomic sequencing to assess varied anthocyanin profiles and associated expression of genes in their biosynthetic pathways. Four key anthocyanins were identified: cyanidin, cyanidin-3-O-rutinoside, delphinidin-3-glucoside, and delphinidin-3-rutinoside. Weighted gene co-expression network analysis (WGCNA) correlated the abundance of these four anthocyanins with transcriptomic data, to suggest three regulatory modules. Nine transcription factors families in these modules were identified and some of them were validated using qRT-PCR. Y2H assay isolated some transcription factors interacted with TTG1 (WD40 protein), including MYB3/39/44/306 and bHLH13/34/110, illustrating the possibility of forming MBW complexes. Our study provides a comprehensive characterization of anthocyanin composition. These findings laid a theoretical foundation for future research on the regulatory mechanisms of pigment accumulation and the breeding of Hippeastrum cultivars with novel petal colors.